Corrected Serum Ionized Calcium as a Risk Factor Related to Adult Dyslipidemia - Yun, Ke; Zhang, Shuang; Yang, Xiaotao; Man, Dongliang; Yao, Jialiang; Wang, Wei; Han, Xiaoxu (Frontiers in Cardiovascular Medicine, 2022)
Background Dyslipidemia is a significant threat to global public health due to its pivotal role as a cardiovascular disease (CVD) risk factor. Calcium is a critical nutritional element required for electrical signal transduction and muscle and heart function, and calcium supplementation is widespread in the general population. However, associations between serum calcium and serum lipid profiles remain conflicting. Considering ionized calcium [Ca(2+)] is the best measure of active serum calcium and the lack of Ca(2+) analyzers, we aimed to examine the independent and joint associations between serum ionized calcium corrected by albumin ([Ca2+]corr) and the known modifiable risk factors and dyslipidemia. Methods We collected physical examination records, including demographic, anthropometric, laboratory tests, and clinical characteristics from individuals who had health checkups in 2019 at the health examination center of the First Affiliated Hospital of China Medical University. Subjects were categorized into Q1–Q4 groups using [Ca2+]corr quartiles, and odds ratios (ORs) with 95% confidence intervals (CIs) for dyslipidemia and associated components were calculated using logistic regression. We also performed non-linear and threshold effect analyses of [Ca2+]corr and triglyceride (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and non-high-density lipoprotein cholesterol (Non-HDL-C) levels. Findings Of 5,416 individuals aged 18–92 years, multivariable-adjusted models showed that ORs for dyslipidemia increased gradually with elevated [Ca2+]corr levels. Logistic regression analyses demonstrated that [Ca2+]corr levels were associated with the increased odds of dyslipidemia (per 1 mmol/L increase: OR = 3.53, 95% CI: 1.56–8.00, P < 0.001). When compared with individuals in the Q1 group, those in groups Q3 and Q4 had significantly higher dyslipidemia odds (ORQ3 vs. Q1 = 1.20, 95% CI: 1.01–1.42; ORQ4 vs. Q1 = 1.31, 95% CI: 1.10–1.56, all P < 0.05). Furthermore, a linear, positive relationship between [Ca2+]corr levels and dyslipidemia odds was observed (P for non-linear trend = 0.506), and the optimal cut-off point of [Ca2+]corr for dyslipidemia management was 2.26 mmol/L. A modifiable effect of albumin on the relationship between [Ca2+]corr and dyslipidemia odds was also found (P for interaction = 0.014). High [Ca2+]corr levels were positively associated with elevated TC, LDL-C, and Non-HDL-C but inversely associated with decreased HDL-C odds. Moreover, Locally weighted regression (Loess) analyses showed a non-linear, positive relationship between [Ca2+]corr and TG, TC, HDL-C, LDL-C, and Non-HDL-C levels. Interpretation Corrected serum ionized calcium was positively associated with increased odds of dyslipidemia and elevated TC, LDL-C, and Non-HDL-C, but inversely associated with the odds of decreased HDL-C.